Multi-Panel CLT Shearwalls: Experimental Assessment, Analytical Development, and Design Considerations - Masroor, Mohammad (Université d'Ottawa / University of Ottawa, 2023)
Analysis and design of Cross-Laminated Timber (CLT) walls under gravity loads have been outlined in the Canadian timber design standard with an adequate amount of details. The methods for designing shearwalls to resist lateral loads have not yet been fully developed, with only concepts being adopted, based on generalized capacity-based design concepts and definitions of yielding and non-yielding components. Several studies have focused on developing analytical expressions and design approaches for multi-panel CLT shearwalls, assuming angle brackets only behave in shear to prevent sliding, while ignoring compression zone effects in CLT panels. These assumptions may simplify the analysis, but they are not practical, especially since contemporary angle brackets are available on the market with uplift capacities comparable to those of hold-down connections. This study aimed to investigate the lateral behaviour of multi-panel CLT shearwalls and provided practical and comprehensive analytical expressions and design procedures for this type of structure. The analysis aimed to integrate the effects of all boundary connections, including hold-downs, angle brackets, panel-to-panel connections, and compression zones, into the analysis. On the basis of the developed analytical expressions, a capacity-based design procedure was proposed, which promoted rocking behaviour and optimized energy dissipation in the shearwall system. A novel yield hierarchy among various connections was introduced, and expressions for associated over-strength factors are proposed. For multi-storey applications, an approach which ensures uniform energy dissipation along the structure height and limits soft-storey failures was also presented. Experimental tests were conducted at the connection level to study the performance of conventional connections used in CLT shearwalls and to obtain their associated mechanical properties. Furthermore, the performance of multi-panel CLT shearwalls was investigated by conducting wall-level experimental tests to investigate the kinematic modes and establish levels of resistance and deflection. Numerical models were developed to verify the mathematical accuracy of the proposed analytical and design expressions. Also, to validate the proposed analytical expressions, they were compared against the numerical models, as well as the wall-level experimental tests. The results showed a reasonable match between the different approaches in terms of the general shape of the curves and kinematic behaviour.
Keywords: CLT shearwalls; Multi-panel; Capacity-based design; Analytical; Seismic; Experimental test; Connections; Yield hierarchy